Sequence Variability in the NRAMP1 Geneamong Indigenous and Exotic Chicken Types - Desmond, Abazuh Uchenna; Olajide, Adekoya Khalid; Olufunmilayo, Oboh Bola (Makara Journal of Science, 2019)
The natural resistance-associated macrophage protein 1 (NRAMP1) gene in chickens, which exists on chromosome 7, is thought to play a significant role in disease resistance. Variations in this gene have been documented and have played crucial roles in the variations in the resistance and/or susceptibility that is expressed by individuals and different groups of animal species. In this study, the NRAMP1 gene was studied for single nucleotide polymorphism (SNP) variability between indigenous and exotic chicken breeds. The gene was amplified using the polymerase chain reaction (PCR) method and sequenced and analyzed. Six SNPs, both synonymous and non-synonymous (C3700T, G3702C, A3712C, C3714G, C3693G, and G3705T), were detected in the gene in both indigenous and exotic chicken types. One allele form was detected among all the sample animals that were studied. A phylogenetic tree revealed that the indigenous chicken type and the exotic broiler chicken type are genetically similar with respect to this gene. However, the exotic layer chicken type is genetically suggested to be distantly related to both the indigenous and broiler chicken types, indi-cating that the gene has probably beenevolving both within and among different poultry species.